2019
DOI: 10.1021/acs.jmedchem.9b01506
|View full text |Cite
|
Sign up to set email alerts
|

Hit-to-Lead Optimization of Benzoxazepinoindazoles As Human African Trypanosomiasis Therapeutics

Abstract: Human African trypanosomiasis (HAT) is a neglected tropical disease caused by infection with either of two subspecies of the parasite Trypanosoma brucei. Due to a lack of economic incentive to develop new drugs, current treatments have severe limitations in terms of safety, efficacy, and ease of administration. In an effort to develop new HAT therapeutics, we report the structure−activity relationships around T. brucei for a series of benzoxazepinoindazoles previously identified through a high-throughput scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Although the number of HAT patients is decreasing every year, many people living in sub-Saharan Africa are still at risk of infection. In the past few years, a number of publications ,, indeed specifically focused on antitrypanosomal drug discovery. Compared to these published scaffolds, the pyrazolopyrimidinones (including 30 ) have a relatively low molecular weight, which is for most of the analogs lower than 300 Dalton.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of HAT patients is decreasing every year, many people living in sub-Saharan Africa are still at risk of infection. In the past few years, a number of publications ,, indeed specifically focused on antitrypanosomal drug discovery. Compared to these published scaffolds, the pyrazolopyrimidinones (including 30 ) have a relatively low molecular weight, which is for most of the analogs lower than 300 Dalton.…”
Section: Discussionmentioning
confidence: 99%
“…We have phenotypically screened compounds that were originally synthesized for ongoing human African trypanosomiasis and Leishmaniasis neglected tropical disease drug discovery programs ( Diaz et al, 2014 ; Bachovchin et al, 2019 ) that yielded benzoxazepinoindazoles ( Klug et al, 2019 ), pyrazolopyridazines ( Tear et al, 2020 ), substituted azaindoles ( Klug et al, 2021 ), and aminopurines ( Singh et al, 2020 ). The imidazopyridines ( Akao et al, 2021 ) were identified by the Drugs for Neglected Diseases initiative (DND i ) via the Neglected Tropical Disease (NTD) Drug Discovery Booster project ( Drugs for Neglected Diseases Initiative, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also identified the EGFR inhibitor ASP-8273 (naquotinib) [21][22][23] as an inhibitor of T. cruzi with good potency (EC 50 of 2.7 nM) and a SI of 191. Several studies have successfully explored kinase inhibitors of trypanosomatids as therapeutic agents [24][25][26], and this compound may represent yet another possible candidate for repurposing or further chemical derivatization.…”
Section: Discussionmentioning
confidence: 99%